Linprot: a multimedia courseware for optimization methods with integration of augmented reality - Raja Noor Farah Azura Raja Maamor Shah (Tanjong Malim, 2019)
Linprot: a multimedia courseware for optimization methods with integration of augmented reality by Raja Noor Farah Azura Raja Maamor Shah